2007
DOI: 10.1097/iae.0b013e3180323de7
|View full text |Cite
|
Sign up to set email alerts
|

Triple Therapy for Choroidal Neovascularization Due to Age-Related Macular Degeneration

Abstract: Purpose:To evaluate the efficacy and safety of triple therapy with verteporfin photodynamic therapy (PDT), dexamethasone, and bevacizumab in choroidal neovascularization (CNV) secondary to age-related macular degeneration (AMD).Methods: This prospective, noncomparative, interventional case series included 104 patients. Verteporfin PDT was administered with a reduced light dose (42 J/cm 2 , accomplished by light delivery time of 70 seconds). Approximately 16 hours after PDT, dexamethasone (800 g) and bevacizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
3
7

Year Published

2007
2007
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 44 publications
3
128
3
7
Order By: Relevance
“…20,26,27 The safety of intravitreal bevacizumab has been confirmed by previous animal studies and human trials, 28,29 and intravitreal injection of bevacizumab has recently been reported to be effective in macular oedema of various etiologies. 20,[30][31][32][33] Results of our study suggest that intravitreal bevacizumab injection appears to be effective in the primary treatment of DME. In our study, 24 eyes showed an improvement in VA with a decrease in fluorescein leakage on FFA (Figure 1a and b).…”
Section: Resultsmentioning
confidence: 67%
“…20,26,27 The safety of intravitreal bevacizumab has been confirmed by previous animal studies and human trials, 28,29 and intravitreal injection of bevacizumab has recently been reported to be effective in macular oedema of various etiologies. 20,[30][31][32][33] Results of our study suggest that intravitreal bevacizumab injection appears to be effective in the primary treatment of DME. In our study, 24 eyes showed an improvement in VA with a decrease in fluorescein leakage on FFA (Figure 1a and b).…”
Section: Resultsmentioning
confidence: 67%
“…[40][41][42] In particular, recent studies have shown that repeated monotherapy with anti-VEGF ranibizumab or bevacizumab may improve vision in patients with CNV of all types. [43][44][45] Sakaguchi et al 46 performed intravitreal bevacizumab (1 mg) injection to treat eight eyes with myopic CNV and improvement of BCVA to two or more lines was found in six eyes (75%).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Moutray et al, 7 in a crosssectional study, observed significant correlation between distance VA and near-word acuity with angiographic parameters such as CNV diameter and area, and leakage area.…”
Section: Introductionmentioning
confidence: 95%